Anti-tumor activity of ginger extracts in MCF-7 breast cancer cells - Faezeh Afshin; Mousa Bohlooli; Ali Maghsoudi; Reza Sheikhnejad; Mostafa Khajeh; Ali Khatibi; Mansour Ghaffari-Moghaddam; Fatemeh Ghamari; Nader Sheibani (Journal of Food and Bioprocess Engineering, 2022)
Breast cancer is the most common form of cancer in women, and the second leading causes of death in the world. Clinical efficacy of chemotherapy is limited due to side effects, toxicity, and drug resistance. Plant-derived anticancer drugs are new promising compounds, which show their anticancer activity through activation of apoptotic pathways. Ginger is a flowering plant with active phenolic compounds that exhibit anticancer activity. Here we studied the effect of ginger acetone, ethanol and methanol extracts on the MCF-7 breast cancer using MTT assay, Real time-PCR and normal inverted microscope. MCF-7 breast cancer cells were incubated with 2.5, 5 and 10 μg/mL of ginger extracts for 48 h. The survival of incubated MCF-7 cells with ginger extracts, indicated significantly decreased. The most dramatic effect was noted in cells incubated with acetone extracts, 10 μg/mL for 48 h compared to the control. Moreover, by increasing the concentration of ethanolic ginger extract, the cell vitality decreased significantly. Real-time PCR results showed that the expression of Bcl-2 was significantly decreased in cells incubated with ginger extracts. Decrease of Bcl-2 expression can cause increase apoptotic pathways and reduction of cancer cell survival. Thus, extract of ginger destroys breast cancer cells and other cancers cells and improves health.